Initial effects of crop tree release and traditional thinning on productivity and carbon storage of Cunninghamia lanceolata plantation - Zou, Xianhua; Zheng, Ziyang; Yang, Chutong; Yang, Mengjia; Guo, Zhijuan; Wang, Yongxin; Huang, Zhijun; Zhu, Liqin; Xu, Liqing; Lin, Kaimin (Frontiers in Forests and Global Change, 2023)
Thinning has a crucial impact on the carbon dynamics of forest ecosystems. This study focuses on Cunninghamia lanceolata as the research object and investigates three treatments: crop tree release (CTR), traditional thinning (TM), and no thinning (CK). The different thinning methods (CTR and TM) have different management objectives and selection of crop trees principle, although with the same thinning density. The short-term effects of CTR and TM treatments on tree growth and carbon storage in Cunninghamia lanceolata plantations were analyzed and compared. The results indicate that both CTR and TM were beneficial to the growth of individual trees when compared to CK, with CTR being more beneficial. The average annual increments in DBH, TH, and volume of a single tree in CTR increased by 62.50%, 61.29%, and 74.07% higher than CK, respectively. So CTR was the best for large-diameter timber yield, which was 77.40% higher than CK, whereas CK had a higher proportion of medium- and small-diameter timber yield. However, CTR had an insignificant short-term boosting effect on stand volume, and its timber volume was considerably higher than that in TM treatment, but not as high as in CK. Therefore, the carbon storage in the tree layer, litter, and different soil layers under different treatments showed that CTR and TM were significantly lower than CK. And the total carbon storage in the three treatments showed that CK > CTR > TM, with CTR showing a 13.07% higher than TM. On the contrary, thinning could effectively improve understory vegetation carbon storage. The carbon storage in the herb and shrub layers under CTR increased by 47.77% and 183.44%, respectively, compared to CK. Therefore, although thinning could significantly promote the growth of individual trees and understory vegetation, their total carbon storage in the short term was lower than that in CK. CTR showed a higher carbon sequestration and sink capacity than TM. It suggests that CTR, as a special type of thinning method, should be encouraged to selected because it has the chance to achieve a faster carbon sequestration rate than traditional thinning and it also can produce higher-quality timber.